Population and the World Bank : adapting to change - World Bank. (Washington, D.C. : World Bank, 2000)
Focuses on how the Bank can increase its effectiveness in population and reproductive health by: 1) linking population to poverty reduction and human development; 2) adapting to diversity and change; 3) being sensitive to country contexts; 4) building on analysis and dialogue and providing sustained support; and 5) strengthening skills and partnerships.
Includes bibliographical references.
oif 09/03/2015
Ref
Keywords: Population policy; Population; Social welfare